Genetic Modification as a New Approach to Ameliorate the Therapeutic Efficacy of Stem Cells in Diabetic Retinopathy. Issue 2 (March 2022) - Lokman Hakim, Nur Yasmin Diana Binti; Noble, Steven; Thomas, Natasya Valentina; Geegana Gamage, Binushi Sandunika; Maxwell, Ganeson-Koo; Govindasamy, Vijayendran; Then, Kong-Yong; Das, Anjan Kumar; Cheong, Soon-Keng
Over the last decades, the strategy of using stem cells has gained a lot of attention in treating many diseases. Recently, DR was identified as one of the common complications experienced by diabetic patients around the world. The current treatment strategy needs to be addressed since the active progression of DR may lead to permanent blindness. Interestingly, varieties of stem cells have emerged to optimize the therapeutic effects. It is also known that stem cells possess multilineage properties and are capable of differentiating, expanding in vitro and undergoing genetic modification. Moreover, modified stem cells have shown to be an ideal resource to prevent the degenerative disease and exhibit promising effects in conferring the migratory, anti-apoptotic, anti-inflammatory and provide better homing for cells into the damaged tissue or organ as well promoting healing properties. Therefore, the understanding of the functional properties of the stem cells may provide the comprehensive guidance to understand the manipulation of stem cells making them useful for long-term therapeutic applications. Hence in this review the potential use and current challenges of genetically modified stem cells to treat DR will be discussed along with its future perspectives.